Testing exponentiality using different entropy estimates based on Type II censored data : A Monte Carlo power comparison - Jarrahi, Jalil; Alizadeh Noughabi, Hadi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The exponential distribution is commonly used to model and examine lifetime data. When applying the exponential model, it is critical to develop efficient goodness of fit tests. In this article, we first propose some new entropy estimators for Type-II censored data and then introduce some goodness of fit test statistics for the exponential distribution based on Type-II censored data using different entropy estimators. The critical values of the tests do not depend on the scale parameter of the exponential distribution and therefore the proposed tests are exact. The critical values and powers of the tests are obtained. The Monte Carlo simulation study indicates that the proposed tests have higher powers than competing tests against the alternatives with monotone increasing hazard functions. Real-life data examples demonstrate the applicability of the proposed tests in practice.